Hubungan Financial Expert CEO dengan Earnings Management saat Perusahaan Melakukan Aksi Korporasi Initial Public Offerings: Studi Kasus Perusahaan Nonkeuangan yang IPO Tahun 2021-2023 - Fitri Takbirani; Nurzi Sebrina (Universitas Negeri Padang, 2026)
This study examines the effect of CEO financial expertise on earnings management in non-financial firms conducting Initial Public Offerings (IPOs) in Indonesia between 2021 and 2023. CEO financial expertise is measured based on educational background and professional experience in the financial sector. Using multiple regression analysis on a sample of 141 firms, this study analyzes the relationship between CEO expertise and both accrual-based earnings management (AEM) and real earnings management (REM).The results show that AEM and REM decrease after the IPO, indicating that earnings management practices are more aggressive during the IPO period. However, CEO financial expertise has no significant effect on either AEM or REM. These findings suggest that financial knowledge alone is insufficient to curb opportunistic reporting behavior in the IPO context. Future research is recommended to explore corporate governance mechanisms as moderating factors in understanding the role of CEO expertise.